Create sustainable value to the customer through the integration of the relationship between total quality management and relationship marketing - القيسي بلال جاسم (Journal of Economics and Administrative Sciences, 2015)
Purpose: This research seeks to provide a point of view based on the creation of sustainable value to the customer of the banks in the context of total quality management and relationship marketing. It aims to develop a model to measure the value of sustainable customer peduncular under total quality management PAL (administrative leadership, involvement of employees, continuous improvement, process improvement, staff training), through the mediation of relationship marketing and objective dimensions (administrative leadership, involvement of employees, continuous improvement, improving processes , staff training), and to explore any of the variables and dimensions more influential in the creation of sustainable value to the customer, this study aimed to discuss the importance of the role of total quality management and its role in achieving the marketing performance in light of relationship marketing and its impact on the Iraqi banking sector, and this study provides scale mode is useful to create sustainable value for the customer, it helps managers to use to assess the current situation in the banking performance, may improve managers their programs more effectively and efficiently through orientation strategy towards strengthening the relationship between the bank and the customer by giving the value they deserve the customer in exchange for a large market share, including reflects on the profitability in the future, all of which depends on the indicators total quality management and its impacts on the creation of value for the customer. Find a problem: the problem of the study summarizes a series of questions, and it was the most important: the elements that enhance the total quality management to achieve sustainable value to the customer of the banks operating in Iraq? What level of impact of total quality management presence or absence of relationship marketing in achieving customer value? Design / methodology: Use approach pilot in the application of the current study, has used the questionnaire to collect data in order to develop a model to measure reliably and correctly to the variables total quality management and marketing relationship with the dimensions of creating sustainable value to the customer, and was selected an intentional sample of managers and heads of departments numbered (119 ) person, and hypotheses were tested through the use of some statistical processors, was the most important path analysis. The most important assumptions are (increasing the impact of total quality management in sustainable value to the customer through the mediation of relationship marketing Results: The sample shows that the interest of the class basis concerning TQM is primarily administrative leadership This finding suggests that the key to success for banks is the mentality of successful leadership is leading banks towards excellence and success within a very competitive environment in the banking sector. Originality / value: undertake this research with the help of service providers in the banking sector to address the challenge of increasing the value provided to the customer, and how to keep the impact of total quality management in order to achieve the best performance marketing.